A True Development Round? A Review of Joseph E. Stiglitz and Andrew Charlton's Fair Trade for All: How Trade Can Promote Development - Lawrence, Robert Z (Journal of Economic Literature, 2007)
In Fair Trade for All: How Trade Can Promote Development, Stiglitz and Charlton prescribe what a multilateral trade agreement—that promotes development and is fair for all—would include. This review appraises their prescriptions and offers some alternatives. Many of their ideas about what developed countries should do (opening markets, especially of labor intensive goods and services and cutting farm subsidies) are quite familiar and sensible. More controversially, however, they propose that all WTO members (both developed and developing) completely open their markets to all developing countries poorer and smaller than themselves. They also stress the importance of preserving domestic policy space, dropping intellectual property rules from the WTO and keeping restrictive rules off the agenda. Among its criticisms of the book, the review points out that the liberalization proposal contradicts their own arguments favoring individually tailored policies in developing countries and is likely to maximize trade diversion. In addition, their prescriptions for more policy space neglects the more desirable possibility of a WTO in which members accept differentiated commitments.